Ecosystem Restoration in Vietnam: Cost, Investment Returns and Carbon Mitigation Benefits - Mirzabaev, Alisher (International Rice Research Institute, 2024)
Vietnam’s valuable ecosystems, ranging from dense forests and grasslands to mangroves and croplands, are experiencing significant degradation due to deforestation, unsustainable land management practices, and climate related stressors. This study assesses the economic and environmental impacts of ecosystem degradation that occurred between 2001 and 2020, estimates the financial investment required for restoring these degraded ecosystems, and quantifies the potential returns in terms of economic gains and carbon mitigation potential. Between 2001 and 2020, approximately 9.5 million hectares of Vietnam’s land underwent changes, with notable transitions including: conversion of grasslands into woodlands, croplands, and agroforestry systems, and deforestation accounting for significant shifts, leading to losses in carbon stocks and ecosystem services. Key findings of this report include: ecosystem degradation in the region has resulted in significant economic losses of $9 billion USD and carbon emissions of 450 million tons. Investing in restoration, particularly in forests and mangroves, offers substantial economic and environmental benefits, with potential returns exceeding investment costs. Identifying and prioritizing key hotspots for restoration is crucial to maximize the impact of these efforts. Restoring Vietnam’s degraded ecosystems presents a critical opportunity to achieve economic, environmental, and social benefits. Strategic investments in restoration of degraded forest, grasslands, and mangrove ecosystems will: support biodiversity and improve rural livelihoods, Strengthen Vietnam’s resilience to climate change, enhance carbon sequestration, contributing to global climate goals. Decision-makers can consider: channeling targeted investments in high-return areas for ecosystem restoration, promoting synergies across land management, biodiversity conservation, and climate mitigation efforts, and leveraging carbon markets and public-private partnerships to mobilize financing for ecosystem restoration. Vietnam’s strong commitment to ecosystem restoration is currently playing an essential role for ensuring sustainable development and enhancing rural prosperity.